1987
DOI: 10.1177/002580248702700405
|View full text |Cite
|
Sign up to set email alerts
|

Police Admissions to Psychiatric Hospitals: A Challenge to Community Psychiatry?

Abstract: Compulsory police admissions from an urban and a rural catchment area with admission rates higher than the national average were studied. A comparison was made with a group of patients admitted involuntarily following assessment by a doctor and a social worker. Police admissions differed in several ways from the comparison group and it is suggested that they were less likely to benefit from hospitalization. Taking into account the likelihood of an increase in the number of contacts between the police and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…However, both this study and previous ones (Fahy et al, 1987)indicate that in prac tice Section 136 often results in patients being brought to a psychiatric hospital to be assessed, and in these instances the distinction between assessment and compulsory admission to hospital is blurred.…”
Section: Commentmentioning
confidence: 69%
See 1 more Smart Citation
“…However, both this study and previous ones (Fahy et al, 1987)indicate that in prac tice Section 136 often results in patients being brought to a psychiatric hospital to be assessed, and in these instances the distinction between assessment and compulsory admission to hospital is blurred.…”
Section: Commentmentioning
confidence: 69%
“…This would raise the question as to why this should be the case. One of the authors (DB) has been involved in looking at areas where there is a high rate of Section 136 admissions (Fahy et al, 1987) and it has been noted that there are a variety of explanations. These include large urban populations with large ethnic minorities and lack of provision of approved social workers.…”
Section: Commentmentioning
confidence: 99%
“…The proportion of men and women detained also matches previous studies that have reported men accounting for slightly more than half of all people detained. 6,9,21 One finding of particular interest was that more than twofifths (41.2%) of all detentions resulted in a discharge without hospital admission. This rate of discharge was considerably higher than those reported in previous research, in which discharge rates of 32%, 10 18%, 5 8%, 6 and even as low as 0.5% 22 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of studies report male gender as a significant characteristic of police referrals (Dunn & Fahy 1990; Evans & Boothroyd 2002; Fahy et al. 1987; Fry & Brunero 2005; Kneebone et al.…”
Section: Literature Reviewmentioning
confidence: 99%